The Role of Virtual Reality in Optimizing Karate Performance: Scoping Review - Dewangga Yudhistira; Muhammad Sukron Fauzi; Naheria Naheria; Didik Cahyono; Kevin Ramadhan; Aprilyan Putra Bimantoro; Shidqi Hamdi Pratama Putra; A. Febi Irawati; Andi Atssam Mappanyukki; Abdul Rahman; Andi Miftahul Jannah (Physical Education Theory and Methodology)
Objectives. The objective of this study was to undertake a scoping review on the role of virtual reality (VR) in optimizing karate performance. The questions to be researched were: (1) how did VR support the training process, (2) what were the challenges of integrating VR, (3) how effective was VR in maximizing performance, and (4) what was the potential of VR  in the development of karate training methods.